In vitro and in vivo activity of ML302F: a thioenolate inhibitor of VIM-subfamily metallo β-lactamases. Issue 1 (25th November 2015) - Betts, Jonathan W.; Phee, Lynette M.; Abdul Momin, Muhd H. F.; Umland, Klaus-Daniel; Brem, Jurgen; Schofield, Christopher J.; Wareham, David W.
Abstract : The thioenol ML302F, recently identified as an inhibitor of class B metallo-β-lactamases (MBLs), restores antibiotic susceptibility to meropenem resistant strains in cells and the Galleria mellonella invertebrate model. Abstract : The thioenol ML302F was recently identified as an inhibitor of class B metallo-β-lactamases (MBLs). We assessed the activity of ML302F when combined with meropenem (MEM) against 31 carbapenem resistant Gram-negative clinical isolates. Minimum inhibitory concentrations of MEM : ML302F were determined at fixed ratios of 1 : 4 and 1 : 8 using strains producing variants of the clinically relevant VIM-like MBL. Toxicity and efficacy in vivo was assessed in a Galleria mellonella invertebrate model against strains producing VIM-1, VIM-2 and VIM-4 variants. At a fixed MEM : ML302F ratio of 1 : 8, 22/31 isolates were rendered either susceptible (MIC ≤ 2 mg L −1 ), or intermediate (MIC 4–8 mg L −1 ) to MEM. ML302F alone was not toxic at up to 80 mg kg −1 in G. mellonella and treatment with MEM 0.6 mg kg −1 : ML302F 4.8 mg kg −1 significantly improved the survival of infected larvae. As ML302F was able to successfully restore susceptibility to resistant strains both in vitro and in vivo it represents a structurally interesting inhibitor in the search for new MBL inhibitors.